2015
DOI: 10.1016/j.bbalip.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic analysis reveals a radiosensitizing role of gamma-linolenic acid in glioma cells

Abstract: Previous studies have demonstrated that gamma-linolenic acid (GLA) is effective against glioma cells under both in vitro and in vivo conditions. In the present study we determined how GLA alone or in combination with irradiation alters the fatty acid (FA) and lipid profiles, the lipid droplet (LD) content, the lipid biosynthetic gene expression and the apoptosis of glioma cells. In GLA-treated cells direct correlations were found between the levels of various FAs and the expression of the corresponding FA bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 77 publications
0
16
0
Order By: Relevance
“…In recent years, it has been found that γ-linolenic acid is cytotoxic to glioma cells, and it can enhance gamma radiosensitivity [ 35 , 36 ]. It has been suggested that this effect is related to the accumulation of the toxic products of lipid peroxidation, which are cytotoxic to glioma cells.…”
Section: Biological Activity Of Evening Primrose Oil ( Omentioning
confidence: 99%
“…In recent years, it has been found that γ-linolenic acid is cytotoxic to glioma cells, and it can enhance gamma radiosensitivity [ 35 , 36 ]. It has been suggested that this effect is related to the accumulation of the toxic products of lipid peroxidation, which are cytotoxic to glioma cells.…”
Section: Biological Activity Of Evening Primrose Oil ( Omentioning
confidence: 99%
“…For example, accumulating evidence points to their importance in inflammation [ 24 ] and in neurodegeneration [ 25 , 26 ]. With respect to stress response, the synthesis of TG and concomitant LD biogenesis was reported to be a hallmark of mammalian cellular stress response [ 24 , 27 , 28 ] and stress response in plants [ 29 ]. In Saccharomyces cerevisiae ( S .…”
Section: Introductionmentioning
confidence: 99%
“…In a similar fashion, PUFAs may also be administered in combination with radiotherapy to enhance the cytotoxic action of radiation on cancer cells and at the same time protect normal cells from the cytotoxic actions of radiation since PUFAs have cytoprotective action on normal cells [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%